EFFECT OF TRANSPARENCY, CASHBACK, AND SECURITY ON INTEREST IN USING GOPAY AS A MEANS OF PAYMENT - Niken Pratami; Ahmad Zuliansyah; Anas Malik (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the influence of Transparency, Cashback, and Security on Generation Z's interest in making e-money payments on Go-Pay. The research methodology used is quantitative descriptive, using the Slovin formula to obtain a population of 100 Generation Z people in Bandar Lampung. The data analysis method used is the data validity test, data reliability test, hypothesis test, and coefficient of determination (R2). The results of the study show that Transparency and security have a positive and significant effect on Generation Z's interest in making e-money payments, with the value of the original sample transparency variable -0.117, the t-statistic value of 2.352, which exceeds the value of 1.96, and the p-value of 0.019, which is smaller than 0.05. Likewise, with the security variable, the original sample value is 0.087, the statistic is 2.945> 1.96 with a p-value of 0.003. On the other hand, the Cashback variable does not have a positive effect on increasing the interest of Generation Z in making payments via e-money, with an original sample value of -0.117, a t-statistic value of 2.352, which is greater than the value of 1.96, and a p-value of 0.019, which is smaller than 0.05.